Phytochemical Analysis, Physical Properties, and Chemical Compound Content White Teak Wood (Gmelina Arborea Roxb) - Ariyanti; Mutmainnah; Asniati (Postgraduate, University of Mataram, 2025)
Indonesia is a country with a tropical climate. Rainfall in Indonesia is quite high and greatly affects the growth of mushrooms (fungi). The use of wood cannot be separated from the manufacture of traditional houses. These traditional houses made of wood are very susceptible to fungal attacks. Wood or wood rot fungi are fungi that live attached to decaying trees, but some types of wood fungi grow on living tree trunks and on dead trees. Wood rot fungi are heterotrophic, or do not produce their own food, This study aims to determine the resistance of white teak wood (Gmelina arborea Roxb) against wood-decay fungi. The research method used was a completely randomized factorial design consisting of two factors: factor I (wood) and factor II (fungi). The test samples used for the combination of the two factors measured 5x 2.50x1.50 cm, with a total of 9 test samples placed in culture jars separately. All samples from the base, middle, and tip tests were placed into a jar containing PSA media, and the inoculated mushroom culture was added to the jar. The observed parameters used an analysis of variance to determine whether the treatment had a significant effect on the decrease in teak wood weight. The Least Significant Difference (LSD) test was carried out to determine whether there were significant differences between treatments or not.